DISAIN DAN PABRIKASI PROTOTIPE PEMBANGKIT LISTRIK TENAGA PIKO HIDRO (PLTPH) KAPASITAS 250 WATT (DC) - Enzo W.B Siahaan; Hodmiantua Sitanggang; Robby Robby; Sari Fitri Siagian (Universitas Quality, 2022)
The pico-hydro power plant is a power plant with a water source as the driving force for the generator. The use of pico hydro has not been popularized in the community so that its utilization has not been maximized. The use of pico-hydro independently can encourage the acceleration of development of underdeveloped areas, because by utilizing pico-hydro it will create a community with independent power plants. This is an alternative way to produce renewable electricity sources because it does not use fuel. The most important components in the manufacture of this machine are the use of pumps, turbines and generators. The working principle of the Pico Hydro Power Plant (PLTPH) is very simple. That is by utilizing the water discharge per second that is in the flow of rivers, irrigation or waterfalls. The flow will be flowed to drive the turbine and will be continued to drive the generator. The expected capacity of this PLTPH prototype is 250 watts (dc). With a power capacity of 250 watts, it is expected to help the community in finding renewable power sources.